Beta-tricalcium phosphate as a synthetic cancellous bone graft in veterinary orthopaedics - Franch, J.; Díaz-Bertrana, C.; Lafuente, P.; Fontecha, P.; Durall, I. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
The clinical use of β-tricalcium phosphate (β-TCP) as a synthetic cancellous bone graft in veterinary orthopaedics is herein reported. The retrospective study was based on 13 clinical cases belonging to 11 dogs and one cat. The weights of the dogs ranged from 3.4 to 48 kg. One female cat weighing 3.5 kg completed the study. The clinical cases were six arthrodeses (four carpal, two tarsal), one hypertrophic non-union (femur), one atrophic non-union (metacarpal bones) and five long-bone fractures (two femurs, one tibia, two radii) possessing subcritical-sized bone defects. The β-TCP used in this study was presented as irregular interconnected-porous granules and was placed in the bone defects after mixing it with fresh blood. Bone healing was achieved at between eight and 12 weeks in all clinical cases except for the case of the chronic atrophic nonunion in which only one of the four metacarpal bones healed. In the 12 successful cases, the bone defect grafted with β-TCP showed a radiological bone ingrowth of 100% (10 cases), 90% (one case) and 75% (one case). The complete lack of tissue adverse effects in our series, and the good defect healing, allows us to hypothesise that β-TCP can be successfully used as a synthetic bone graft in bone defects with good local biological conditions and where osteoconduction is especially needed for assuring a structural scaffold for newbone ingrowth. When, in addition to osteoconduction, osteoinduction and osteogenesis are necessary for defect healing, the fresh cancellous bone graft remains the gold standard in veterinary orthopaedics.
Keywords: β-tricalcium phosphate; bone grafting